3D inversion recovery ultrashort echo time MRI can detect demyelination in cuprizone-treated mice - Searleman, Adam C.; Ma, Yajun; Sampath, Srihari; Sampath, Srinath; Bussell, Robert; Chang, Eric Y.; Deaton, Lisa; Schumacher, Andrew M.; Du, Jiang (Frontiers in Neuroimaging, 2024)
Purpose: To test the ability of inversion-recovery ultrashort echo time (IR-UTE) MRI to directly detect demyelination in mice using a standard cuprizone mouse model.Non-aqueous myelin protons have ultrashort T2s and are "invisible" with conventional MRI sequences but can be detected with UTE sequences. The IR-UTE sequence uses an adiabatic inversion-recovery preparation to suppress the long T2 water signal so that the remaining signal is from the ultrashort T2 myelin component. In this study, eight 8-weekold C57BL/6 mice were fed cuprizone (n = 4) or control chow (n = 4) for five weeks and then imaged by 3D IR-UTE MRI. The differences in IR-UTE signal were compared in the major white matter tracts in the brain and correlated with the Luxol Fast Blue histochemical marker of myelin.Results: Cuprizone-treated mice demonstrated decreased IR-UTE signal in the white matter tracts known to be sensitive to cuprizone but not in white matter tracts known to be resistant, while control mice showed no change in IR-UTE signal in all white matter tractsIR-UTE signal demyelination in this model, such as the corpus callosum, but not in white matter known to be resistant to demyelination, such as the internal capsule. These findings correlated with histochemical staining of myelin content.Conclusions: 3D IR-UTE MRI was sensitive to cuprizone-induced demyelination in the mouse brain, and is a promising noninvasive method for measuring brain myelin content.